Język wrażliwy na płeć w edukacji. Analiza wybranych dokumentów uniwersyteckich - Sawicka, Julia (Kultura-Społeczeństwo-Edukacja, 2021)
The purpose of the article is to discuss issues related to the gender-sensitive language used in education, as well as how feminine forms function in Polish language. In particular, the documents analyzed are those used at Adam Mickiewicz University in Poznan. The basic question that underlies the discussion here refers to gender-specific asymmetry in language and its impact on shaping reality.